Synchronous multicentric small hepatocellular carcinomas: defining the capsule on high-frequency intraoperative ultrasonography with pathologic correlation - Ahn, Jae Hong (Ultrasonography, 2016)
PURPOSE: The aim of this study was to define the capsules of synchronous multicentric small hepatocellular carcinomas (HCCs) with use of high-frequency intraoperative ultrasonography (IOUS). METHODS: Among the 131 consecutive patients undergoing hepatic resection and high-frequency IOUS for HCC, 16 synchronous multicentric small HCCs in 13 patients were histologically diagnosed in the resected specimens. High-frequency IOUS and pathologic findings of these lesions were compared, with particular focus on the presence and appearance of the capsule in or around each lesion. RESULTS: Synchronous multicentric small HCCs were pathologically classified into distinctly nodular (n=12) or vaguely nodular (n=4) types. All 12 distinctly nodular HCCs including six subcentimeter lesions showed detectable capsules on high-frequency IOUS and pathology. The capsules appeared as a hypoechoic rim containing hyperechoic foci (n=6), hypoechoic rim (n=5), or hyperechoic rim (n=1) with varying degrees of coverage around each lesion. Histologically, the capsules were composed of a combination of one to four layers consisting of a fibrous capsule, peritumoral fibrosis, prominent small vessels, and entrapped hepatic parenchyma. CONCLUSION: Synchronous multicentric small HCCs with distinctly nodular type, even at subcentimeter size, can show capsules with varying coverage and diverse echogenicity on high-frequency IOUS.